Aggressive Treatment in Glioblastoma: What Determines the Survival of Patients? - Yu, Lei; Zhang, Guozhong; Qi, Songtao (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background and Study Aims The exact reason of long-term survival in glioblastoma (GBM) patients has remained uncertain. Molecular parameters in addition to histology to define malignant gliomas are hoped to facilitate clinical, experimental, and epidemiological studies.Material and Methods A population of GBM patients with similar clinical characteristics (especially similar resectability) was reviewed to compare the molecular variables between poor (overall survival [OS] < 18 months, control cohort) and long-term survivors (overall survival > 36 months, OS-36 cohort).Results Long-term GBM survivors were younger. In the OS-36 cohort, the positive rate of isocitrate dehydrogenase (IDH) mutation was very low (7.69%, 3/39) and there was no statistical difference in OS between IDH mutant and wild-type patients. The results of 1p/19q codeletions are similar. Besides, there were no significant difference in MGMT promoter methylation, telomerase reverse transcriptase (TERT) promoter mutation, and TP53 mutations between OS-36 cohort and control cohort.Conclusions No distinct markers consistently have been identified in long-term survivors of GBM patients, and great importance should be attached to further understand the biological characteristics of the invasive glioma cells because of the nature of diffuse tumor permeation.
Keywords: glioblastoma; long-term survival; IDH1; 1p/19q codeletions; MGMT; TERT